Influence of Government Policy on Economic Efficiency : Case of Ukraine and Georgia - Korolko, Mariya; Frömmel, Tomáš; Slaný, Martin, 1982-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2018)
The purpose of this thesis is to analyze the extent to which economic reforms in Georgia after the 2004 Rose Revolution and Ukraine after the 2014 revolution influence economic growth. The outcome of the thesis is that economic reforms such as privatization, liberalization and de-bureaucratization indeed influence per capita growth rate, however, promotion of limited governmental interference is not always beneficial for the economy. The results suggest that currently Ukrainian government should not focus on promotion of foreign direct investment, but rather on increasing government integrity. Whereas Georgia should focus on increasing financial freedom. Moreover, the thesis shows that limitation of governmental influence is not always the key to economic growth.
Vedoucí práce: Tomáš Frömmel
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses